EXTREMISM BETWEEN THE CHURCH IN THE MEDIAEVAL AGES AND AL KHAWARIDGE - Ibrahem, Muhammad Kh. (Journal of Tikrit University for Humanities, 2020)
Non-finite thanks are due to almighty Allah and the best blessings of Allah be upon his best creature the prophet Muhammad (peace and blessings be upon him and his fellows).The presented research under the chosen title ( Extremism between the Church in the Mediaeval Ages and AL Khawaridge). The reason behind choosing this topic is to clarify the similarities between the concept of extremism which was ruled by the church in the mediaeval ages and AL Khawaridge under the name of extremists and expiation in our modern life. The main reason that urges me to write this research is to show how the church nowadays spreads the moderation accuses Islam and considers Muslims as terrorists while they commit plenty of crimes and kill lots of people. The research tries to clarify how the unbelievers focuses on specific issues in Islam and deform the clear picture of Islamic letter that is transferred by the prophet Muhammad (peace and blessings of Allah the almighty be upon him) in which all the rights of humans are reserved especially their lives while the church leaders named the Muslims and their religion as terrorists by referring to the ISIS (Da3sh) as the sample for other Muslims. This research consists of an introduction and four sections. The last part of the study is the conclusion.